ALIVE© virtual learning approach enhances student engagement and academic performance - Naqiah, Puaad (UMPSA, 2025)
PEKAN, 6 February 2025 – Active Lightboard Virtual Education (ALIVE©) is a virtual learning approach that has been shown to enhance student engagement and academic performance.